The “Turkey story”: A critical narrative analysis of a potential “Brexit conspiracy” - Alma-Pierre Bonnet (ELAD-SILDA)
Extensive academic literature has been devoted to the way “Brexit narratives” were used during the 2016 referendum campaign. Both camps dwelt on this rhetorical tool to create stories about the advantages of leaving or staying in the European Union (EU). Overall, studies have revealed the construction of broadly similar stories, in particular within the “populist narratives” of the Leave campaign, which depicted the EU as a “failure”, an “oppressor”, and an object of anti-establishment “fury”. Within the field of narratology, cognitive linguistics and conspiratorial studies, this paper proposes a discursive analysis focused on one particular narrative which, we argue, has received relatively little attention but which might constitute an example of “Brexit conspiracy”: what we call “the Turkey story”. Indeed, one key element in the Brexit narratives elaborated by the official pro-Brexit campaign, Vote Leave, was the fact that Turkey, and other poorer – and predominantly Muslim – countries, were “in the pipeline” to join the EU. At first marginal, this story soon took centre-stage to justify the necessity to leave the supra-national organization before “hordes” of illegal immigrants from those countries, and from neighbouring Iraq and Syria, decided to emigrate en masse to Britain. Thanks to the narrative analysis of speeches and declarations by leading Vote Leave members, this paper sets to examine whether “the Turkey story” amounts to a conspiracy theory and how it was used to defend the anti-EU agenda, which will lead to the introduction of the concept of “strategic conspiracy”.